INSTAGRAM FOLLOWERS AS DIGITAL ASSETS FOR MSMEs ACTORS IN PALU CITY - Jannah, Miftahul; Muslimin, Muslimin; Darman, Darman (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This study aims to find out MSMEs actors in Palu City in understanding Instagram followers as digital assets. The qualitative research method was carried out through a phenomenological approach, used to examine more closely and in detail understanding and explanation of individuals based on their experiences. Sources of data applied in this study are primary data and secondary data. Through the study of phenomenological awareness, the researcher has explored the awareness of informants regarding the meaning of Instagram followers. Based on the results of data analysis that has been carried out and synergize the meanings found in several meanings through reflection. How do the informants understand the meaning of Instagram followers as an asset starting with making it a necessity that can bring profits, posting freely, sacrifices, digital assets, and a sense of loss. It means that the informant has reached the point of awareness in interpreting Instagram followers as digital assets. Keywords: Followers, Instagram, Digital Assets, and UMKM